Pengaruh Daya Tahan dan Kecepatan, terhadap Kinerja Wasit Sepakbola C1 Nasional PSSI Provinsi Riau - Agus Prima Aspa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the effect of endurance and speed on the performance of the National C1 football referee PSSI Riau Province. This study uses a quantitative approach with path analysis, the population in this study is the National C1 referee, amounting to 38 people, the sampling technique uses the Total Sampling technique that is the same sampling technique with the population, which is used as a sample for a total population of 38 referees National C1. Data were collected using match commissioner reports to measure referee performance, fitness tests to measure endurance and run 40 meters to measure speed. The results of the data analysis show that the path coefficient is significant and linear, where the magnitude of the direct effect is as follows: 1). The results of the endurance analysis showed a value of 9.30%. 2). The results of the speed analysis showed an amount of 7.45%. Conclusions based on the results of the research analysis and discussion, the following conclusions can be drawn. 1) there is a direct influence of endurance on the performance of the National C1 soccer referee, 2) there is an immediate effect on speed on the performance of football referee Keywords: Endurance, Speed ​​, and Referee Performance.